Review of Progress in Quantitative Nondestructive Evaluation 1997
DOI: 10.1007/978-1-4615-5947-4_160
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Ultrasound with a Partially Contacting Solid-Solid Interface in the Low Frequency Regime

Abstract: INTRODUCTIONWhen real engineering surfaces touch, contact occurs between the asperities of the surface roughness. Forthis reason the true area of contact between components can be significantly less than the apparent contact area and the stresses at the asperities are considerably higher than the average (nominal) contact pressure. Measurement ofthe degree of contact between solids is important in a number of applications such as the design of contacting elements (e.g. gears and bearings) [1] and the detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 10 publications
2
30
0
Order By: Relevance
“…The interaction of ultrasonic waves with interfaces formed by two non-conforming, rough surfaces in contact has been the subject of numerous investigations [1][2][3][4][5][6][7][8][9][10]. The motivations behind these studies have been various: from the assessment of the real area of contact between two rough surfaces [I], to the modeling of crack closure near the tip of a fatigue crack [4]; from the identification of the nature of interfacial imperfections in kissing and partial bonds [6], to the generation of ultrasonic waves [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of ultrasonic waves with interfaces formed by two non-conforming, rough surfaces in contact has been the subject of numerous investigations [1][2][3][4][5][6][7][8][9][10]. The motivations behind these studies have been various: from the assessment of the real area of contact between two rough surfaces [I], to the modeling of crack closure near the tip of a fatigue crack [4]; from the identification of the nature of interfacial imperfections in kissing and partial bonds [6], to the generation of ultrasonic waves [8].…”
Section: Introductionmentioning
confidence: 99%
“…The motivations behind these studies have been various: from the assessment of the real area of contact between two rough surfaces [I], to the modeling of crack closure near the tip of a fatigue crack [4]; from the identification of the nature of interfacial imperfections in kissing and partial bonds [6], to the generation of ultrasonic waves [8]. In most of these studies, the characterization of the interfacial properties has been attempted by studying the reflection of longitudinal and shears waves at normal incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, solid rubber coupling would be more desirable in these applications. Solid coupled ultrasonic transducers employ a soft solid, typically rubber, padding between the transducer and the test piece, which conforms to the surface contour [7][8][9]. However, special lowattenuation rubbers have inherently high stiffness requiring relatively thick rubber cushions to conform to the irregular surface therefore the transmission loss is still significant.…”
Section: Coupling Between the Transducer And The Test Specimenmentioning
confidence: 99%
“…Possible corrections are discussed in [18,19). The interfacial stiffness between two contracted rough surfaces has been measured ultrasonically by several authors [12,14,15]. Also, several studies have been performed to estimate it theoretically [18,19]).…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%
“…When the interphasiallayer containing imperfections is thin and the imperfections are flat the interphasiallayer can be modeled as an infinitely thin interface with distributed springs to account for interfacial stiffness reduction due to imperfections [1]. Significant effort has been put into experimental and theoretical studies of ultrasonic wave interaction with imperfect interfaces [1]- [15] with the goal of characterizing interface imperfections by the ultrasonic signature. It has been shown that by measuring the frequency response of the coefficient of reflection from an interface with spring boundalY conditions one can determine the interfacial spring stiffness.…”
Section: Introductionmentioning
confidence: 99%